Сільські господарства Глухівщини: про населення м. Дубовичі та навколишніх хуторів (за переписом 1920 р.) - Іванченко, Л.А. (Сіверщина в історії України, 2023)
Уперше представлено статистичні відомості про населення містечка Дубовичі з найближчими населеними пунктами Глухівського повіту Чернігівської губернії (сучасної Сумщини) за подвірним переписом 1920 р. Викладено демографічні показники щодо місцевих жителів із зазначенням соціальних даних, економічної діяльності та з топографічною прив’язкою. Statistical information on the population of the town of Dubovychi and nearby farms is given according to the homestead census of 1920. At that time the territory was located in Hlukhiv district of Chernihiv province (Sumy region at present). 1920 was in fact the first year when Russian-Bolshevik regime - also called Soviet power - was being established on the territory of Ukraine. The census form to be filled in had the following graphs: surname, first name, middle name of the owner, address, citizenship, social status; for family members: gender, age, marital status and family ties, education, occupation; the list of craft property, agricultural means of labor, cattle, the size of the manor lands, crops, etc. Such indicators in the newly created state were basic information to do forecasting and management of socio-economic development, taxation, migration, ideological policy, as well as the indicator of human resources that could form an army. This information is being made public for the first time.